PRINCIPLE OF CABOTAGE WITHIN AVIATION ACTIVITIES IN INDONESIA - Harry Purwanto (Fakultas Hukum Universitas Gadjah Mada, 2016)
Liberalization their logging services makes the concept of cabotage which was known in the field of shipping, has now become part of the field of aviation. Such a situation when associated with the concept of state sovereignty in the air space, juridically has caused a serious intersection. In countries that do not accept the concept of air cabotage, often found smuggling air cabotage laws. Thus requiring the state government concerned to judicial action in order to protect its national airline company, including the Government of Indonesia. Adanya Liberalisasi jasa penebangan menjadikan konsep cabotage yang tadinya dikenal dalam bidang pelayaran, kini menjadi bagian dalam bidang penerbangan. Situasi demikian bila dikaitkan dengan konsep kedaulatan negara di ruang udara, secara yuridis telah menimbulkan persinggungan yang cukup serius. Pada negara yang belum menerima konsep cabotage udara, sering ditemukan penyelundupan hukum cabotage udara. Sehingga mengharuskan pemerintah negara yang bersangkutan melakukan tindakan yuridis dalam rangka melindungi perusahaan penerbangan nasionalnya, termasuk Pemerintah Indonesia.